Effectiveness of the application of bawang dayak (eleutherine palmifolia l. merr) extracts on healing proccess in the osteitis alveolar post tooth extraction through fibroblast examination, collagen density and amount of osteogenesis (experimental study) - Fajar Rezandaru; Endang Syamsudin; Indra Hadikrishna; Vetnizah Juniantito (Journal of Dentomaxillofacial Science, 2020)
Objectives: The aim of this study was to analyze the potential for topical administration of Eleutherine palmifolia (l.) merr extract gel in the healing proccess of wound with osteitis alveolar as a complication after tooth extraction in Sprague dawley mice by observing fibroblast cell area, collagen density, and amount of osteogenesis.Material and Methods: This study used a true experimental research method conducted on Sprague Dawley mice. Sample were divided into 3 groups, namely K1 (osteitis alveolar was not given any treatment), K2 (osteitis alveolar mice were given iodoform paste application every 3 days), and K3 (osteitis alveolar mice were given application of the extract gel Eleutherine palmifolia (l.) merr topically). On day 3, 5 and 10 necropsy was done and the tooth sockets in the form of soft tissue together with hard tissue was taken, then preparations were made and stained with masson trichrome to examined fibroblasts, collagen and osteogenesis.Results: Topical application of the extract gel Eleutherine palmifolia (l.) merr showed the mean value of fibroblasts area and collagen density and the amount of osteogenesis were comparable to iodoform paste in alveolar osteitis healing.Conclusion: this study is that the application of Eleutherine Palmifolia (l) merr extract gel has almost the same effectiveness as iodoform paste